Genetic diversity of pigmented rice landraces (Oryza sativa) from South Sumatra, Indonesia revealed by SSR markers - LAILA HANUM; TUTIK WAHYUNI; YADI OKTARIANSYAH (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Hanum L, Wahyuni T, Oktariansyah Y. 2026. Genetic diversity of pigmented rice landraces (Oryza sativa) from South Sumatra, Indonesia revealed by SSR markers. Biodiversitas 27 (1): d270130. https://doi.org/10.13057/biodiv/d270130. Pigmented rice landraces constitute an important component of Indonesia’s rice genetic resources, yet information on their molecular diversity in South Sumatra remains limited. This study tested the hypothesis that pigmented rice landraces from South Sumatra exhibit SSR-detectable genetic variation among accessions, whereas genome-wide differentiation between pigmentation groups (red and black rice) is weak or non-significant. This study assessed the genetic diversity and relatedness of ten local pigmented rice (Oryza sativa) landraces, comprising seven red and three black rice accessions, using 11 Simple Sequence Repeat (SSR) markers. All markers produced clear and reproducible amplification profiles, generating fragments ranging from 127 to 480 bp, with six to twelve alleles per locus. Marker informativeness was consistently high, with PIC values of 0.790-0.917 (mean = 0.878), indicating strong discriminatory power for accession differentiation. SSR profiles were predominantly homozygous, reflecting the autogamous reproductive system of rice, although limited heterozygosity was detected at a few loci in specific accessions. Multilocus comparison revealed moderate divergence among landraces, supported by Jaccard similarity coefficients ranging from 0.769 to 1.000. UPGMA clustering resolved a structured pattern consisting of a closely related core group of accessions, an intermediate subgroup represented by Linggau and Tanjung Agung, and a more divergent subgroup comprising Sumber Jaya and Teluk Tenggirik. However, AMOVA indicated that molecular variation was predominantly distributed within populations (100%) rather than among populations (0%), with a non-significant differentiation between red and black rice groups (Fst = -0.038; p = 0.769). These findings provide baseline molecular evidence supporting conservation prioritization and highlight genetically distinct landraces as potential donors for future pigmented rice breeding programs. This study represents one of the few SSR-based molecular assessments focusing specifically on pigmented rice landraces from South Sumatra, Indonesia.